Penggunaan Wondershare Quiz Creator Sebagai Media Evaluasi Pembelajaran Bahasa Arab - Piliana, Baiq Jannatul; Suparmanto, Suparmanto; Maskaturrohmi, Lina; Mutiah, Khufyatil; Ikhwan, Ahmad (Lugatuna : Jurnal Prodi PBA, 2024)
This study assesses the use of Wondershare Quiz Creator as an assessment tool in teaching Arabic in MAN 2 Model Mataram. Wondershare Quiz Creator is a software that allows us to create interactive quizzes to assess how well students understand the material being taught. This research uses classroom action research that involves several cycles: Planning, implementation, observation, and reflection. The results of the study show that this software can increase student engagement and motivation. However, technical issues such as difficult access and unstable internet connections often hinder the learning and evaluation process, reducing the efficiency of assessment. However, students' evaluation scores increase by 10% compared to conventional evaluation methods, when the software is well accessible. The results show that Wondershare Quiz Creator can improve the quality of Arabic learning evaluation, but to use it better, accessibility issues must be solved.